Role of Little Magazine in Bengali Literature: Challenging Elitist Clichés: Redefining Bengali Refugee Identity in Literature and Film (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this proposition, I problematize the predominance of East Bengali bhadralok outsider's memory with regards to scholarly social talks on the Partition of Bengal (1947). By examining post-Partition Bengali literature and film delivered by upper-rank uppermiddleclass East Bengali foreigner specialists, for example, Jyotirmoyee Devi's epic The River Churning and Ritwik Ghatak's film The Cloud-Capped Star, I show how sanctioned works of art have propounded elitist clichés to the burden of the non-bhadra displaced people's portrayals. To challenge these works, I contrast them and points of view accessible in other outcast essayists' writings. These incorporate Dalit original literates' encounters, as depicted in Adhir Biswas' diaries Deshbhager Smriti. This examination extends the learning of Bengali displaced person personality in India past fixed bhadralok settler delivered generalizations, in light of a legitimate concern for an increasingly libertarian and complex comprehension.